2013
DOI: 10.2106/jbjs.j.01989
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the Radial Head and Neck

Abstract: The majority of simple fractures of the radial head are stable, even when displaced 2 mm. Articular fragmentation and comminution can be seen in stable fracture patterns and are not absolute indications for operative treatment. Preservation and/or restoration of radiocapitellar contact is critical to coronal plane and longitudinal stability of the elbow and forearm. Partial and complete articular fractures of the radial head should be differentiated. Important fracture characteristics impacting treatment inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 70 publications
0
43
0
8
Order By: Relevance
“…In 1979 (27) and then in 1988 (28) Morrey et al demonstrated that the radial head contributes to the valgus, varus and posterolateral rotatory stability of the elbow and acts as an axial stabilizer of the forearm; because of these biomechanical studies and along with significant improvement in surgical techniques and instrumentation, open reduction and internal fixation has become the preferred treatment for Mason type II fractures. At present, a fracture fragment displacement of ≥ 2 mm is usually used as a criterion for operative treatment (29); as a matter of fact, different parameters should be taken into account when planning the best treatment to perform (30,31): type of fracture, displacement, fragment stability, magnitude of articular involvement, and presence of associated complex injuries. In the case of a stable and isolated Mason type II fracture, mid-and long-term follow up studies have demonstrated that nonsurgical treatment can provide good or excellent functional outcome in the vast majority of cases (32,33,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In 1979 (27) and then in 1988 (28) Morrey et al demonstrated that the radial head contributes to the valgus, varus and posterolateral rotatory stability of the elbow and acts as an axial stabilizer of the forearm; because of these biomechanical studies and along with significant improvement in surgical techniques and instrumentation, open reduction and internal fixation has become the preferred treatment for Mason type II fractures. At present, a fracture fragment displacement of ≥ 2 mm is usually used as a criterion for operative treatment (29); as a matter of fact, different parameters should be taken into account when planning the best treatment to perform (30,31): type of fracture, displacement, fragment stability, magnitude of articular involvement, and presence of associated complex injuries. In the case of a stable and isolated Mason type II fracture, mid-and long-term follow up studies have demonstrated that nonsurgical treatment can provide good or excellent functional outcome in the vast majority of cases (32,33,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the anatomical variance of the proximal radius and ulna and have aimed at establishing guidelines to achieve proper osteosynthesis and avoid proximal radioulnar joint (PRUJ) impingement. 10,23,28 Inadvertent intra-articular screw penetration can lead to early joint degeneration, pain, and loss of function. 24 Lindenhovius et al evaluated 16 patients who underwent plate fixation for fractures of the radial head.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment options are available, depending on fracture severity. [5,6] Although biological treatment modalities, such as conservative methods and open reduction and internal fixation, are first-choice treatments, [7] especially for Mason Type-III fractures, the optimum treatment method remains controversial. [5,6] Results of radial head resection (RHR) [8,9] and radial head prosthesis…”
mentioning
confidence: 99%